Emile Durkheim.
1 online resource (xvi, 1040 pages)
Keywords: This four volume set is dedicated to the work of Emile Durkheim, one of the most important and prolific sociologists in the field, whois commonly cited as a founding fatherof modern social science. With volumes published between 1975 and 1991, this collection brings together a range of moderncritical responses to Durkheim's work across a broad range of topics, including: epistemology, modernism and post-modernism, theories of social order, and the rise and development of modern society. The authors in the collection also draw important comparisons between Durkheim and other seminal sociologists, including Max Weber and Claude Bernard.For institutional purchases for e-book sets please contact online.sales@tandf.co.uk (customers in the UK, Europe and Rest of World)